Cardiovascular adverse events associated with targeted therapies for multiple myeloma: a pharmacovigilance study - Zhang, Yanli; Shan, Chang; Zhang, Xinxin; Liu, Ying; Xia, Yunlong; Wang, Yanfeng (Frontiers in Immunology, 2024)
Multiple myeloma (MM) is a leading cause of hematopoietic cancer-related mortality, accounting for 20% of deaths. MM-targeted therapies have demonstrated efficacy, and since 2015, the United States Food and Drug Administration (FDA) has approved five targeted drugs. However, their cardiovascular safety has not been comprehensively evaluated.This study aimed to investigate the association between MM-targeted therapy and cardiovascular adverse events (AEs).Disproportionality analysis was conducted on reports from the FDA AE Reporting System database from 2014 to the second quarter of 2023. Cardiovascular AEs were grouped into nine narrow categories using the Standardized Medical Dictionary for Regulatory Activities Queries (SMQs)A total of 3,228 cardiovascular AE cases involving MM-targeted therapy were extracted and analyzed. Significant disproportionality was identified for daratumumab, elotuzumab, and isatuximab. Among the nine narrow SMQ categories, the three most reported cardiovascular AEs were cardiomyopathy, cardiac arrhythmias, and embolic and thrombotic events. Noninfectious myocarditis/pericarditis, cardiac arrhythmias, and embolic and thrombotic events exhibited the strongest signal strengths. The cardiovascular AE risk was higher within the first month and gradually decreased thereafter; however, it increased rapidly again after one year. This trend was observed for all cardiovascular AEs. The Kaplan-Meier curve and the log-rank test revealed that isatuximab and elotuzumab exhibited a significantly lower probability of cardiovascular AEs than daratumumab (P<0.001).MM-targeted therapy is significantly associated with an increased risk of previously unknown cardiovascular AE profiles, with the range and onset differing among various drugs, thereby warranting specific monitoring and appropriate management.